Take a Trip Through the Plant and Fungal Transportome of Mycorrhiza - Garcia, Kevin; Doidy, Joan; Zimmermann, Sabine D.; Wipf, Daniel; Courty, Pierre-Emmanuel (Trends in plant science, 2016)
Soil nutrient acquisition and exchanges through symbiotic plant–fungus interactions in the rhizosphere are key features for the current agricultural and environmental challenges. Improved crop yield and plant mineral nutrition through a fungal symbiont has been widely described. In return, the host plant supplies carbon substrates to its fungal partner. We review here recent progress on molecular players of membrane transport involved in nutritional exchanges between mycorrhizal plants and fungi. We cover the transportome, from the transport proteins involved in sugar fluxes from plants towards fungi, to the uptake from the soil and exchange of nitrogen, phosphate, potassium, sulfate, and water. Together, these advances in the comprehension of the mycorrhizal transportome will help in developing the future engineering of new agro-ecological systems. Plant growth and development are highly dependent on rhizosphere nutrient availability which is often a limiting factor. This constraint has forced land plants to evolve various strategies, including beneficial interactions with soil microorganisms. The symbiotic interactions between plant roots and fungi, termed mycorrhizal symbiosis, provide reciprocal benefits for both partners, as for instance for the plant partner the acquisition of nitrogen (N), phosphate (P), potassium (K), and sulfate (S), the primary macronutrients used in plant fertilizer. Plant and fungal transport systems display ‘mycorrhiza-specific’ and ‘fine-tuning’ regulation to control nutrient fluxes towards the symbiotic interface, delimiting the site of reciprocal nutrient exchanges between the partners. The selection and engineering of mycorrhizal partners based on the plant and fungal transportome, targeting the key transporters resulting from the massive generation and analysis of ‘omics’ data, will ensure agro-ecological improvement of crop nutrition.